MTORC1 and DNA‐PKcs as novel molecular determinants of sensitivity to Chk1 inhibition. Issue 1 (25th August 2015) - Massey, Andrew J.; Stephens, Peter; Rawlinson, Rebecca; McGurk, Lauren; Plummer, Ruth; Curtin, Nicola J.
Abstract : Background: Chk1 inhibitors are currently under clinical evaluation as single agents and in combination with cytotoxic chemotherapy. Understanding determinants of sensitivity and novel combinations is critical for further clinical development. Potentiation of mTOR inhibitor cytotoxicity by the Chk1 inhibitor V158411 was determined in p53 mutant colon cancer cells. DNA damage response, expression levels of repair proteins, cell cycle effects and the contribution of alternative DSB repair pathways were further evaluated by western blotting and high content analysis. Results: mTOR inhibitors AZD8055, RAD‐001, rapamycin and BEZ235 induced synergistic cytotoxicity with the Chk1 inhibitor V158411 in p53 mutant colon cancer cells. Reduced FANCD2, RAD51 and RPA70, core proteins in homologous recombination repair (HRR) and interstrand crosslink repair (ICLR), following inhibition of mTOR was associated with increased V158411 induced DSBs and caspase 3‐independent cell death. Dual mTOR and Chk1 inhibition activated DNA‐PKcs. Cells defective in DNA‐PKcs exhibited increased resistance to V158411 with Chk1 expression closely correlated to DNA‐PKcs expression in various types of cancer. Conclusions: Down regulation of proteins involved in HRR or ICLR by mTOR inhibitors is associated with increased sensitivity of human tumours to Chk1 inhibitors such as V158411. High levels of DNA‐PKcs may be a potential biomarker to stratify patients to Chk1 inhibitor therapy alone or in combination with mTOR inhibitors. Highlights: mTOR inhibitors induce synergistic cytotoxicity with V158411. mTOR inhibition increases V158411 induced DNA DSBs. Mechanism through regulation of HR and ICL repair proteins by mTOR. DNA‐PKcs overexpressing cells were more sensitive to Chk1 inhibition. Correlation between CHEK1 and PRKDC (DNA‐PKcs) mRNA levels in human tumour samples.